U.K. Banking After Deregulation - Mullineux, A. W. (London ; New York : Croom Helm, 1987)
The book addresses the effects of financial deregulation and the development of an electronic banking system in a survey of UK change in the financial sector and in banking in particular.
"Published in the USA by Croom Helm in association with Methuen ... New York, NY"--T.p. verso.
Includes index.
Bibliography: p. 166-171.
osc 9/8/17
Loans
Keywords: Banks and Banking; Banks and Banking